2011
DOI: 10.2337/db10-0802
|View full text |Cite
|
Sign up to set email alerts
|

The Central Sirtuin 1/p53 Pathway Is Essential for the Orexigenic Action of Ghrelin

Abstract: OBJECTIVEGhrelin is a stomach-derived peptide that increases food intake through the activation of hypothalamic AMP-activated protein kinase (AMPK). However, the molecular mechanisms initiated by the activation of the ghrelin receptor, which in turn lead to AMPK activation, remain unclear. Sirtuin 1 (SIRT1) is a deacetylase activated in response to calorie restriction that acts through the tumor suppressor gene p53. We tested the hypothesis that the central SIRT1/p53 pathway might be mediating the orexigenic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
138
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(146 citation statements)
references
References 40 publications
(48 reference statements)
7
138
0
1
Order By: Relevance
“…This is the first study in which the GHRL effect on the four main neuropeptides involved in the metabolic regulation of food intake have been assessed simultaneously. The observed changes are in concordance with those previously observed in mammals in which central GHRL administration resulted in consistent increases of NPY and AgRP expression (Andrews et al 2008, Sangiao-Alvarellos et al 2010, Martins et al 2013, Stark et al 2015 and, occasionally, in decreased POMC and CART mRNA levels (Velásquez et al 2011).…”
Section: Ghrl Treatment Inhibits Fatty Acid-sensing Systems Increasinsupporting
confidence: 80%
See 2 more Smart Citations
“…This is the first study in which the GHRL effect on the four main neuropeptides involved in the metabolic regulation of food intake have been assessed simultaneously. The observed changes are in concordance with those previously observed in mammals in which central GHRL administration resulted in consistent increases of NPY and AgRP expression (Andrews et al 2008, Sangiao-Alvarellos et al 2010, Martins et al 2013, Stark et al 2015 and, occasionally, in decreased POMC and CART mRNA levels (Velásquez et al 2011).…”
Section: Ghrl Treatment Inhibits Fatty Acid-sensing Systems Increasinsupporting
confidence: 80%
“…The orexigenic effect is in agreement with that observed in most fish species after IP or ICV GHRL treatments (Unniappan et al 2002, Tinoco et al 2014, and is in line to the effect of this peptide in other vertebrates, including mammals (Ló pez et al 2008, Sangiao-Alvarellos et al 2010, Velásquez et al 2011, Martins et al 2013, Stark et al 2015. It is surprising that GHRL did not also increase food intake 6 h after treatment.…”
Section: Ghrl Treatment Inhibits Fatty Acid-sensing Systems Increasinsupporting
confidence: 71%
See 1 more Smart Citation
“…Finally, the postprandial suppression of AMPK was eliminated in UCP2 knockout but not in wild type mice (Andrews et al, 2008). More recent studies have also indicated the roles of Sirtuin 1 (SIRT1)/p53 (Velasquez et al, 2011) and CPT1c/ceramide (Ramirez et al, 2013) in the orexigenic effect of ghrelin signalling.…”
Section: Central Ghrelin Signalling and Food Intakementioning
confidence: 81%
“…Nonetheless, the weight of evidence indicates that SIRT1 in the agouti-related peptide-producing neurons (AgRPs) controls the response to the gut hormone ghrelin and feeding behavior (Dietrich et al 2010(Dietrich et al , 2012Sasaki et al 2010). In addition, SIRT1 in the ventromedial hypothalamic (VMH) neurons determines physiological outputs to ghrelin signaling (Velasquez et al 2011;Porteiro et al 2013). SIRT1 in the dorsomedial hypothalamus (DMH) and lateral hypothalamus (LH) is induced by CR and mediates outputs such as physical activity and body temperature by determining the levels of the orexin receptor 2 (Satoh et al 2010).…”
Section: Hypothalamusmentioning
confidence: 99%